[ 50-(7/9-11/12+1/6)×(-6)的平方]÷(-7)的平方
1个回答
=[50-(28/36-33/36+6/36)x36]/49
=[50-(28-33+6)/36 x36]/49
=(50-1)/49
=49/49
=1
相关问题
(-1)的平方-【1又3/7+(-12)÷6】的平方×(-3/4)
( 11 12 - 2 3 )÷ 11 24 (1+ 7 9 )×18 7 8 ÷ 35 36 × 5 6 4 9 ×
-1平方-[1又3/7+(-12)÷6]平方×(-3/4)立方=
1×2÷3×4÷5×6÷7×8÷9×10÷11×12
6/7×5/9+4/9×6/7(简便计算) 0.8-(2/3+1/12)×8/9 5/6÷(6-5/12-7/12
①21.6÷4 ②1.6÷50 ③9.09÷0.9 ④1.5×3.5 ⑤18×3.7 ⑥6.09×5.7 &
简便计算.2.5×1.25×32 13 6 ÷ 7 5 - 1 6 × 5 7 7 12 ×13+ 11 12 ×7.
1+2+3+4+5+6+7+8+9+10÷11÷12×0=?
能简算的要简算 12 13 × 3 7 + 4 7 × 12 13 + 12 13 9.6-11÷7+ 1 7 ×4 3
直接写得数:2/7×14/15=?6/7÷3=?12÷6/11=?3/4÷9/16=?25×40%=?20×【1/4-1